EFFECTS OF A COMBINATION THERAPY WITH ATORVASTATIN AND METFORMIN ON THE GLYCEMIC CONTROL AND ADIPOSITY INDICES IN NEWLY DIAGNOSED OVERWEIGHT PATIENTS WITH TYPE 2 DIABETES MELLITUS: A PILOT STUDY - Mohammed, Samer Shukur; Mustafa, Wael Waleed; Hussain, Saad Abdulrahman (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: In many type 2 diabetes mellitus (T2DM) patients, metformin is prescribed concomitantly with hypolipidemic agents, particularly statins. Meanwhile, variability in response to metformin is one of the most important problems in the efficacy of this combination. The present study aims to evaluate the effect of adding atorvastatin with metformin on the glycemic control, adiposity indices, and lipid profile of overweight patients newly diagnosed with type T2DM. Methods: A total of 50 overweight patients with T2DM were allocated into two groups, the first one received 850 mg/day of sustained release metformin and the second group received 10 mg/day atorvastatin in addition to the metformin. The patients were followed for 90 days through evaluating fasting serum glucose (FSG), glycated hemoglobin (HbA1c), body mass index (BMI), visceral adiposity index (VAI), and the lipid profile at baseline and after 90 days. In addition, the safety of the protocol was monitored through the evaluation of the renal and liver functions. Results: HbA1c, FSG, BMI, and VAI values were significantly decreased in both treatment groups compared with baseline. Meanwhile, the combination improves all the lipid profile components with respect to the baseline. No significant differences reported between the two groups regarding all the measured parameters. The addition of atorvastatin produced a slight but significant negative impact on the renal and liver functions. Conclusion: Addition of 10 mg/day atorvastatin with metformin in the treatment of newly diagnosed T2DM overweight patients did not produce significant improvement in glycemic control, adiposity index, and lipid profile compared with the use of metformin alone.